2010
DOI: 10.1096/fj.09-148452
|View full text |Cite
|
Sign up to set email alerts
|

In vivo nutrigenomic effects of virgin olive oil polyphenols within the frame of the Mediterranean diet: a randomized controlled trial

Abstract: The aim of the study was to assess whether benefits associated with the traditional Mediterranean diet (TMD) and virgin olive oil (VOO) consumption could be mediated through changes in the expression of atherosclerosis-related genes. A randomized, parallel, controlled clinical trial in healthy volunteers (n=90) aged 20 to 50 yr was performed. Three-month intervention groups were as follows: 1) TMD with VOO (TMD+VOO), 2) TMD with washed virgin olive oil (TMD+WOO), and 3) control with participants' habitual diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
1
15

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(237 citation statements)
references
References 61 publications
8
196
1
15
Order By: Relevance
“…These results are in line with previous human and animal studies showing that phenolic compounds present in virgin olive oil exert benecial cardiovascular effects, particularly improving the lipid prole. 8,10,31 In fact, the European Food Safety Authority has recently issued a positive opinion on the capacity of olive oil phenolic compounds to protect LDL cholesterol from oxidative damage. 32 Several markers show that rats in the present study suffered hepatic stress induced by the cholesterol-rich diet, which may have led to an incipient insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with previous human and animal studies showing that phenolic compounds present in virgin olive oil exert benecial cardiovascular effects, particularly improving the lipid prole. 8,10,31 In fact, the European Food Safety Authority has recently issued a positive opinion on the capacity of olive oil phenolic compounds to protect LDL cholesterol from oxidative damage. 32 Several markers show that rats in the present study suffered hepatic stress induced by the cholesterol-rich diet, which may have led to an incipient insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Virgin olive oil (VOO) is an essential component of the traditional Mediterranean diet, and attracts the interest of the scientific community for its health-promoting properties [1][2][3][4][5][6]. VOO is unique for its high levels of monounsaturated fatty acids and the presence of a wide range of minor components that are largely responsible for both their health-promoting properties and their organoleptic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 3-wk consumption of VOO as a principal fat source for healthy human volunteers in a diet low in natural antioxidants, upregulates 10 genes (ADAM17, ALDH1A1, BIRC1, ERCC5, LIAS, OGT, PPARBP, TNFSF10, USP48, and XRCC5) related to prevention atherosclerosis development and progression [117]. Recently, in a randomized controlled trial, it was observed that VOO intake decreases plasma oxidative and inflammatory status and the gene expression related with both inflammation [INF-gamma (INFgamma), Rho GTPase-activating protein15 (ARHGAP15), interleukin-7 receptor (IL7R)] and oxidative stress [adrenergic beta(2)-receptor (ADRB2) and polymerase (DNA-directed)] in PBMNCs [118].…”
Section: Discussionmentioning
confidence: 99%